Exercise With Low-Loads and Concurrent Partial Blood Flow Restriction Combined With Patient Education in Females Suffering From Gluteal Tendinopathy: A Feasibility Study - Høgsholt, Mathias; Jørgensen, Stian Langgård; Rolving, Nanna; Mechlenburg, Inger; Tønning, Lisa Urup; Bohn, Marie Bagger (Frontiers in Sports and Active Living, 2022)
Introduction: To date, there exists no gold standard conservative treatment for lateral hip pain due to tendinopathy of the gluteus medius and/or minimus tendon (GT), a condition often complicated by pain and disability. Higher loads during everyday activities and exercise seems to be contraindicated with GT. The purpose of this study was to evaluate the feasibility of exercise with low-loads concurrent partial blood flow restriction (LL-BFR) and patient education for patients present GT. Methods: Recruitment took place at three hospitals in the Central Denmark Region. The intervention consisted of daily sessions for 8 weeks with one weekly supervised session. From week three patients exercised with applied partial blood flow restriction by means of a pneumatic cuff around the proximal thigh of the affected leg. Throughout the intervention patients received patient education on their hip condition. Sociodemographic and clinical variables were collected at baseline. The feasibility of LL-BFR was conducted by adherence to the exercise protocol and drop-out rate. Patient reported outcome measures (The Victorian Institute of Sport Assessment-Gluteal Questionnaire, EuroQol - 5 Dimensions-Visual Analogue Scale, Oxford Hip Score, Copenhagen Hip and Groin Outcome Score), maximal voluntary isometric hip abduction-, hip extension, and knee extension strength (Nm/kg) measured using a handheld dynamometer, and functional capacity tests (30 second chair-stand test and a stair-climb test) was conducted as secondary outcomes. Results: Sixteen women with a median (IQR) age of 51 (46-60) years were included. Median (IQR) Body Mass Index was 26.69 (23.59-30.46) kg/m2. Adherence to the total number of trainingsessions and the LL-BFR was 96.4% and 94.4%, respectively. Two patients dropped out due to i) illness before initiation of LL-BFR and ii) pain in the affected leg related to the LL-BFR-exercise. At follow-up both pain levels and patient-reported outcome measures improved. Isometric hip abduction-, hip extension-, and knee extension strength on both legs and functional performance increased. Conclusion: LL-BFR-exercise seems feasible for treatment of GT. At follow-up, a high adherence and low drop-out rate were observed. Further, patients reported clinically relevant reductions in pain, and showed significant increases in isometric hip and knee strength.